Making sense of the social world : methods of investigation - Chambliss, Daniel F.; Schutt, Russell K. (Thousand Oaks, Calif. : Pine Forge Press, 2006)
In this Second Edition of the bestselling Making Sense of the Social World: Methods of Investigation, authors Daniel F. Chambliss and Russell K. Schutt once again provide students with an engaging, innovative, and accurate introduction to social research. More than a brief derivative of the Fifth Edition of Schutt's Investigating the Social World, this version is written in a less format, occasionally humorous style, with more concise examples drawn from everyday experience and less coverage of complex or more rigorous methods."--Jacket.
Includes bibliographical references and index.
Keywords: Social problems -- Research; Social sciences -- Research